Coto Makassar Legend - Rahaman, Radzi; Sulaiman, Mohd Iman; Rubama, Alahasin; Salie, Awang Saubrie; Inson, Elvin Edika; Louis, Brendon (2017)
Coto Makassar Legend is a business food corner located in UiTM, Kota Kinabalu, Sabah that allows the students and staffs to enjoy a true taste of the original recipe coto makassar. The main course of Coto Makassar Legend is the coto makassar, and we also serve other foods and drinks. The members in Coto Makassar Legend company wants to served food fast and convenient to the students and staff in the university. While there are many other restaurants in Kota Kinabalu that served coto makassar, Coto Makassar Legend will excel because of the recipe that we used in our main course compare to our competitors. We believed that the recipe can give big impact and attract lot of customers everyday. From our direct observation, most restaurants in Kota Kinabalu, they treated their coto makassar with creamer to make their base soup milkier. After doing our research and interview to the family that run coto makassar business since 1970s, coto makassar came from Indonesia and the recipe reach Sandakan Sabah around the year. For the based soup, they used (recipe bumbu) to make a big impact when a person slurp the soup. The (lada) is also special homemade which synchronize with the (kacang) and enhance the flavor and make the person addicted and want to eat more. The prove is that this family's original recipe was always order as catered by Sabah Ministry, like the latest event, served 5000 people. Thus, we see this a good business opportunity. We, Coto Makassar Legend, believed that this opportunity has the potential of success provided that it is handled with expert. The students have always needed to treat themselves with warm and good meal. A meal can become a good factor towards student motivation and contribute energy. Therefore, by taking all the advantage, we believe we can run the business for a very long term and maintain our friendship.